2016
DOI: 10.1513/annalsats.201508-525oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function before and after a Large Chlorine Gas Release in Graniteville, South Carolina

Abstract: Rationale: On January 6, 2005 a train derailment led to an estimated 54,915-kg release of chlorine at a local textile mill in Graniteville, South Carolina.Objectives: We used the employee health spirometry records of the textile to identify enduring effects of chlorine gas exposure resulting from the incident on the lung function of workers employed at the textile mill.Methods: Spirometry records from 1,807 mill workers (7,332 observations) were used from 4 years before and 18 months after the disaster. Longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Over the 3 years following the chlorine release, rates of hospitalization and emergency department visits for ambulatory care–sensitive conditions increased significantly in the Graniteville population compared with a nearby population not exposed to chlorine . In the year following the accident, Graniteville millworkers had significantly reduced FEV 1 , and the prevalence of millworkers with accelerated FEV 1 decline was increased …”
Section: Persistent Effects Of Chlorine Exposure In Humansmentioning
confidence: 99%
“…Over the 3 years following the chlorine release, rates of hospitalization and emergency department visits for ambulatory care–sensitive conditions increased significantly in the Graniteville population compared with a nearby population not exposed to chlorine . In the year following the accident, Graniteville millworkers had significantly reduced FEV 1 , and the prevalence of millworkers with accelerated FEV 1 decline was increased …”
Section: Persistent Effects Of Chlorine Exposure In Humansmentioning
confidence: 99%
“…Exposure to chlorine can occur through household accidents, occupational exposures, and accidental train derailments during chlorine transportation (Evans, 2005; Van Sickle et al, 2009; White and Martin, 2010). When inhaled, chlorine produces adverse acute health effects such as hypoxemia, airway obstruction, and pulmonary edema (Das and Blanc, 1993; Van Sickle et al, 2009; White and Martin, 2010) and long-term effects including respiratory symptoms and altered lung function (Schwartz et al, 1990; Malo et al, 2009; Clark et al, 2016). In a subset of individuals accidentally exposed to high levels of chlorine, such exposures have been associated with a condition termed acute irritant-induced asthma or reactive airways dysfunction syndrome (RADS), which is characterized by airway obstruction and hyperreactivity (Donnelly and FitzGerald, 1990; Malo et al, 2009; Chierakul et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Graniteville cohort, 59 which now has 305 patients enrolled, is the only systematic long-term longitudinal cohort study of a population exposed to a single high-concentration Cl 2 gas event with pre-post individual exposure and health comparisons and prospective longitudinal lung function assessment. In the cohort, it was observed that the immediate lung function loss between 2004 and 2005 14 had not fully recovered at 7-9 years postevent for some individuals. Furthermore, surprisingly, 12% of the participants were medically ineligible for spirometry testing owing to their high blood pressure even after repeated attempts to medically control it, and the modeled Cl 2 dose was significantly associated with their increased blood pressure (P < 0.05) 7-9 years later.…”
Section: Cardiovascular Effects Of CL 2 Toxicitymentioning
confidence: 96%
“…This is the largest civilian U.S. population ever exposed to Cl 2 gas . Data have been aggregated from 1979 to 2006 for over 8000 Graniteville millworkers who have at least 3 years of pre‐event spirometry and related health and covariate assessment . Individual Cl 2 exposures from the event have been estimated using validated plume models .…”
Section: Chlorine As An Occupational and Public Health Hazardmentioning
confidence: 99%